Talent Management Concepts: Analysis Recruitment, Program Training, Mentoring, and Leadership - Indra Rustiawan; Rubadi; Ratna Tri Hari Safariningsih; Agustian Zen (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to find factors that influence talent management. The purpose of this article is to identify and summarize literature reviews related to recruitment, training, mentoring, and management, and to review the findings of the variables considered and the impact of one variable on another. am. This study uses a literature search by looking for variable references in several international articles. This study provides an overview of incoming articles describing the effects between variables. Results showed that several variables influenced the exposure index matrix. The research on talent management in this literature review article focuses specifically on the variables that can potentially improve talent management effectively recruitment, training, mentoring, and leadership.